THE EFFECT OF SERT (SELF-EXPLANATION READING TECHNIQUE) UPON STUDENTS READING COMPETENCY: AN EXPERIMENTAL STUDY CONDUCTED ON THE STUDENT OF MANAGEMENT PROGRAM IN UNDIKNAS UNIVERSITY IN 2016/2017 - Ida Nyoman Basmantra (Universitas Pendidikan Nasional, 2017)
This study aimed at analyzing whether or not there was a significant difference in the students’ reading competency taught through SERT and Conventional Reading Technique. The population of this study was the students of management program in Undiknas University. This study uses the null hypothesis, so there is no significant difference between the two groups of students taught through the SERT and Conventional Reading Techniques. To obtain research objectives, Post-Test Only Control Group Design is applied as a research design. Both classes are randomly selected as samples. Data obtained from the post-test were analyzed using Descriptive and Inferential Statistics Analysis. In the descriptive analysis, it was found that the average score of the experimental group was 8.19 while the mean score of the control group was 7.26, which means that the experimental group performed better than the control group. In the inferential statistical analysis, the difference in students taught through the SERT and Conventional Reading Techniques proved significant in the 5 percent (0.5) alpha significance level in which the observed t value (5.758) was higher than the critical value t (1.96); thus the null hypothesis is rejected. Based on the findings, it is concluded that H0 (Null Hypothesis) stating that the SERT (Reading Engineering Self-Explanation) = Conventional Reading Technique is rejected and Ha (Alternative Hypothesis) stating that the SERT (Self-Explanatory Reading Technique)? Conventional Reading Techniques are accepted, in which students with SERT treatment are better than Conventional Reading Techniques.